Mentoring of community service nurses in North West Province, South Africa: A convergent parallel mixed method study results - Sisinyana Hannah Khunou; Zodwa Margaret Manyisa (Elsevier, 2022)
This article reports on merged findings regarding mentoring of community service nurses (CSNs) at public health facilities in North West Province (NWP), South Africa. The study was part of a main study on development of a mentoring for CSNs at NWP public facilities.Mentoring has been described as a crucial human resource strategy which promotes support and adequate socialisation of newly qualified nurses into the profession. The purpose of this study was to explore and describe perceptions of CSNs and nurse managers regarding mentoring of CSNs in NWP public health facilities.Convergent parallel mixed method design was adopted, whereby both quantitative and qualitative approaches were applied concurrently to collect data regarding their perceptions about mentoring of CSN in NWP public health facilities. Population consisted of a total 531 CSNs and 341 nurse managers. Purposive sampling was used to obtain 28 CSNs and 27 Nurse Managers who participated in semi-structured interviews. Stratified random sampling was used to select 224 CSNs and 174 nurse managers who completed the mentoring perceptions questionnaires. Qualitative data was transcribed and analysed with Atlas ti7 software. Descriptive statistics was used to analyse quantitative data using Statistical Package for Social Science (SPSS) version 23. Themes which emanted from merged result highlighted negative and positive perceptions regarding mentoring of CSNs. Both participants in merged results were in agreement pertaining to mentoring needs. Inconsistencies was noted with regard to challenges pertaining to perfomance of community service.